The Storytelling Method in Javanese Assisted by Loose Parts Media for Kindergarten Children - Hadi Purwoko; Santoso; Fitri Budi Suryani (Universitas Pendidikan Ganesha, 2022)
The ability to communicate in children is still low and has yet to develop according to expectations and age stages. Children can interact less and communicate properly and correctly with their environment. This research aims to create a storytelling method assisted by loose parts media to improve Javanese language skills in kindergarten. This type of research is development research, with this research method referring to the theory of Borg and Gall. Data collection techniques used were interviews, observations, and questionnaires. The analysis used in this study was quantitative and qualitative. The subjects of this study were kindergarten teachers and students. The material expert validation process assessment obtained an average result of 3.83 with a percentage of 95%, including the very good category. Linguists get an average result of 3.67 with a percentage of 92%, and the category is very good. The teacher's response obtained an average of 3.63, scoring 30 in the very good category. The child's response obtained an average result of 3.68 with a total score of 138 in the very good category. The results of calculating N-Gain in the field test as an experimental class obtained post-test results of 80.67 and 80.33, respectively, while for the control class, the post-test obtained results of 56.00. The results show that developing Javanese storytelling methods with the help of loose parts media for kindergarten children is feasible and effective in improving children's Javanese language skills.